Rice bran supplementation modulates environmental enteric dysfunction markers and serum metabolites in weaning Nicaraguan infants - Zambrana Gutiérrez, Luis Enrique, author; Ryan, Elizabeth, advisor; Legare, Marie, committee member; Weir, Tiffany, committee member (Colorado State University. Libraries, 2018)
Rice bran (RB) is an agricultural byproduct from whole grain rice processing. It is an accessible, underutilized food ingredient that merits global health research attention to improve nutritional security, reduce childhood malnutrition, and mitigate environmental enteric dysfunction (EED). The objective was to analyze the effects of dietary RB supplementation on growth, EED biomarkers, and serum metabolites in healthy, weaning infants from six-to-twelve months old residing in León, Nicaragua. Effects of dietary RB supplementation on growth and EED biomarkers were examined after a six-month feeding period. Five-month-old infants (n=71) were screened for eligibility and 62 infants were randomized, for a prospective clinical trial (NCT02615886). The randomization was done within the health sector where each child belongs and by sex to either be allocated to RB dietary group or control group without RB consumption. Weight and length measurements and stool samples were collected at 6 (baseline), 8 and 12 months of age. Blood was collected at 12 months only. Stool and serum EED biomarkers were compared between study groups. Two-sample t-tests were used to compare weight and length between the two groups, and a non-parametric Wilcoxon Rank-Sum test was used to test differences for EED biomarkers. Targeted and non-targeted serum metabolite profiling was completed by using liquid chromatography tandem-mass spectroscopy. The RB group had significantly increased length-for-age Z-score (LAZ) from 6 to 8 months, and 6 to 12 months compared to control (p<0.01). RB participants showed decreased intestinal permeability and inflammation in the stool marker Alpha-1-Antitrypsin (p=0.02) and beneficial effects on gut function in the serum Glucagon-like-peptide-2 (p<0.04). Fifty-four serum metabolites were significantly different following RB supplementations versus control. These results support multiple favorable outcomes from RB supplementation in weaning infants. Findings from this pilot study support that RB intake during weaning is safe, promotes healthy intestinal functions, and enhances growth outcomes.